ANALYTICAL SOLUTION FOR SIMPLY SUPPORTED LAMINATED COMPOSITE PLATES BASED ON PARTIAL LAYERWISE THEORY - Rakočević, Marina (Journal of Applied Engineering Science, 2016)
Anisotropic composition of layered composite plates requires more accurate mathematical and calculation models. By applying Reddy’s layerwise theory we can cover a wide range of problems of layered composite plates with arbitrary arrangement of layers through the plate thickness. The analytical method of solving bending equations in Layerwise Theory is based on the assumed displacement field in the form of the double trigonometric Fourier's series. The analytical solution can be used as a test solution for solutions obtained by using numerical methods, including finite element method. For Partial Layerwise Theory, the paper presents the equations of bending for laminated composite plates and the algorithm for calculation of deflections and stresses in an arbitrary cross section of a simply supported rectangular plate loaded with distributed load. On the basis of the algorithm presented in this paper, author has prepared Fortran program called ANSLACOP (ANalytical SOlution of LAminated COmposite Plates), whose structure will be presented in the paper. It is presented that the solution obtained by using this program very quickly converges depending on the adopted number of members of double trigonometric series.